2011
DOI: 10.1002/ppul.21589
|View full text |Cite
|
Sign up to set email alerts
|

Lung function distinguishes preschool children with CF from healthy controls in a multi‐center setting

Abstract: Spirometry appears more sensitive than IP or FO for detecting lung disease in CF preschoolers; spirometric indices decline with age. Future trials using spirometry should include a run-in period for training and require acceptable data prior to enrollment. However, near-normal spirometric measurements in CF preschoolers may lead to difficulty detecting a treatment effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
(38 reference statements)
3
40
0
Order By: Relevance
“…However, there is evidence of tracking of spirometry outcomes over this period [63], and also evidence that children who are infected with Pseudomonas aeruginosa early in life have persistently lower spirometry outcomes than their uninfected peers [63]. Data from the recent US multicentre data suggest that spirometry outcomes are more discriminative than outcomes from forced oscillation or inductance plethysmography [78].…”
Section: Preschool Lung Functionmentioning
confidence: 99%
“…However, there is evidence of tracking of spirometry outcomes over this period [63], and also evidence that children who are infected with Pseudomonas aeruginosa early in life have persistently lower spirometry outcomes than their uninfected peers [63]. Data from the recent US multicentre data suggest that spirometry outcomes are more discriminative than outcomes from forced oscillation or inductance plethysmography [78].…”
Section: Preschool Lung Functionmentioning
confidence: 99%
“…Subsequently, graduates of the IPFT study who were aged between 36 and 60 months of age were enrolled in a longitudinal study of preschool lung function [10,11] Requirement for inclusion in the current analysis was enrolment in both the infant and preschool study and at least one acceptable IPFT and one acceptable preschool spirometry test. Most participants in the current study were diagnosed following clinical presentation as universal newborn screening was available at only one of the six centres at the time of enrolment. Detailed eligibility criteria for the IPFT and preschool lung function studies have been previously published [9][10][11]. Informed consent was obtained from all parents/guardians and institutional review board approval was obtained at all centres.…”
Section: Participantsmentioning
confidence: 99%
“…DAVIS et al [9] recently reported mild but progressive obstructive lung disease in a multicentre US cohort of CF infants using the raised volume rapid thoracic compression (RVRTC) technique and whole-body plethysmography. A subset of these children subsequently enrolled in a multicentre study of preschool lung function [10,11]. Infant pulmonary function tests (IPFTs) are increasingly being employed to monitor early CF lung disease in the hopes that early detection of disease may improve outcomes.…”
mentioning
confidence: 99%
“…The largest FEVt and FVC should be reported even if not taken from the same manoeuvre, and forced expiratory flows are taken from the manoeuvre with the largest sum of FEV0.5 and FVC [37]. In an experienced laboratory, acceptable spirometry can be obtained in over 75% of pre-school children, and success rates increase with age [39,40]. Between-test reproducibility is good for FEV0.5, FEV1 and FVC (intraclass correlation coefficient (ICC) 0.85-0.92) and moderate for FEF25-75 (ICC 0.60) [39].…”
Section: Pre-school Spirometrymentioning
confidence: 99%